LIABILITY IN SPACE LAW: QUESTIONS ON PRACTICAL APPLICATION OF ABSOLUTE AND FAULT LIABILITY (The Pretoria Student Law Review, 2021)
With modern advances in technology, mankind is now faced with new legal problems and situations previously unanticipated. Space law in particular is relevant as, while most of the documents were drafted and assented to in the mid 1990’s, there have since been great advances in space exploration and technology. This means that potential situations exist which are not expressly provided for in International Space Law. Therefore, since the answers for hypothetical questions cannot always be found explicitly in space law, we will be relying on the sources of international law listed in article 38(1) of the International Court of Justice Statutes, namely international conventions, international custom, general principles of law and judicial decisions and teachings.1 The rules of the Vienna Convention regarding the interpretation of Treaties must also be kept in mind, including that a state is obliged to refrain from acts that would defeat the object and purpose of a treaty that it has ratified. There are therefore two main questions that will be discussed in this article: whether a state can be held absolutely liable for its actions if it, in changing the course of an asteroid affect the area of damage and whether a state can be held liable on the basis of fault for damage caused by its space craft to another space craft if the damage was anticipated and the second state was warned not to be in that specific location.
Keywords: Space law; international law; International Court of Justice Statutes; Vienna Convention; absolute state liability; asteroid affect; fault for damage